Directed-evolution approach to empower EGFR targeting for immunotherapy - Bunyarit Meksiriporn; Jamie B. Spangler (Cell Reports Methods, 2024)
Advances in directed-evolution technologies are enabling new strategies to isolate binding proteins that recognize disease-associated states of a target protein. In this issue of Cell Reports Methods, Dobersberger et al. devised a yeast display-based selection scheme to discover proteins that engage the cancer-associated activated state of a receptor to enable design of safe and effective immunotherapies.
Keywords: CAR-T cell therapy research; Viral Infectious Diseases and Gene Expression in Insects; Monoclonal and Polyclonal Antibodies Research